Matharpacady-09.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Bounding Matharpacady on the west, Mascarenhas Road is named after Dr M. Ubaldo Mascarenhas, who hailed from Bastora village, Bardez, Goa. An Indian freedom fighter who was evicted from Goa, he later became the 19th Mayor of Mumbai (1948–49). The descendants of his family still live at 16 Matharpacady. The family includes Dr Gerald Mascarehnas and Dr Allwyn Mascarenhas (D. Ubaldo’s grandnephews), who serve the community as medical doctors. Another descendant, Vincent Mascarenhas, is the current president of the Matharpacady Holy Cross Committee.